Study of Wind Characteristics and Key Monitoring Points for Traffic Control in Nanjiang Railway - Hongkai YAN; Xinmin PAN; Wenjun YE (机车电传动)
Strong wind is one of the most serious meteorological disasters affecting railway transportation safety, by which the first hundred kilometers of wind area along Nanjiang railway of the China Railway Urumqi Group Co., Ltd. is the most severely affected. In order to further reduce traffic safety risks and improve the level of operation organization and management, it was necessary to introduce the short-time local strong wind forecast, and form a new mode of train traffic control under the command of strong wind forecast and measured data. Wind data by hours in the first hundred kilometers of wind area along Nanjiang railway from 2015 to 2018, as well as the history data of traffic scheduling command from November 2014 to October 2015 were analyzed, and the key data that affects the choice of traffic scheduling command were chosen, including 5 key wind speed monitoring points in 4 traffic areas, which provided the accurate position for the maximum wind speed point, ensuring the security of the railway train operation in wind season.